ICT as an Enabler of Transformation in Ethiopia - Lixi, Marc; Dahan, Mariana (World Bank, Washington, DC, 2014)
Over the last two decades, Ethiopia has achieved remarkable progress toward social and economic indicators. Analytical evidence shows that development projects with a significant information and communication technology (ICT) component have a higher potential to achieve greater outcomes on the ground than the ones not supported by ICT. This is why the Government of Ethiopia sees ICT within the broader context of its socioeconomic development objectives and believes that it should take advantage of today's most innovative and reliable technologies to accelerate the rate of economic growth and alleviate poverty in the country. The Government of Ethiopia has requested the ICT sector unit of the World Bank to prepare a comprehensive report on how ICT can be used to achieve a true transformation of the Ethiopian economy and society. Therefore, this report explores how ICT can be leveraged to foster the development of an ICT-enabled industry and the private sector in general, to enhance public sector performance, to develop the agriculture and health sectors, and finally how all these efforts can lead to the emergence of an open innovation ecosystem. This report takes stock of current and recently-launched ICT initiatives in Ethiopia and develops sector-specific recommendations based on international best practices that help leverage the transformative power of ICT to improve the social and economic well-being of citizens and achieve rapid and sustainable socioeconomic development. The report explores following topics: background in chapter one, presents fostering the development of ICT-enabled industry and the private sector in chapter two. Chapter three deals with enhancing the performance of the public sector. Chapter four is developing the health sector. Chapter five deals with agricultural and rural development. Chapter six helps in creating an open innovation ecosystem; and chapter seven presents recommendations for ICT-enabled transformation in Ethiopia.